2016
DOI: 10.1016/j.jiph.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance of Aeromonas hydrophila isolated from different food sources: A mini-review

Abstract: Aeromonas hydrophila is a Gram-negative, oxidase-positive, facultative, anaerobic, opportunistic aquatic pathogen. A. hydrophila produces virulence factors, such as hemolysins, aerolysins, adhesins, enterotoxins, phospholipase and lipase. In addition to isolation from aquatic sources, A. hydrophila has been isolated from meat and meat products, milk and dairy products, and vegetables. However, various studies showed that this opportunistic pathogen is resistant to commercial antibiotics. This is attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
152
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(172 citation statements)
references
References 40 publications
14
152
1
5
Order By: Relevance
“…(). While we identified that only 14% of the isolates possessed bla OXA , other studies reported higher percentages as reviewed previously (Stratev and Odeyemi ). Our findings also identified bla CTX‐M , which is responsible for the hydrolysis of CTX, only in 24% of the isolated A. hydrophila .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…(). While we identified that only 14% of the isolates possessed bla OXA , other studies reported higher percentages as reviewed previously (Stratev and Odeyemi ). Our findings also identified bla CTX‐M , which is responsible for the hydrolysis of CTX, only in 24% of the isolated A. hydrophila .…”
Section: Discussionsupporting
confidence: 67%
“…The resistance of A. hydrophila isolated from freshwater fish to antimicrobial agents differs among various studies (Stratev and Odeyemi ). However, it is difficult to compare our results with that obtained in other studies from Egypt due to the dearth of information about antimicrobial resistance of A. hydrophila from mullet.…”
Section: Discussionmentioning
confidence: 99%
“…É muito importante monitorar bactérias patogênicas em áreas de praia porque a propagação da poluição nas zonas de banho está diretamente ligada à saúde dos banhistas de mar, tornando a poluição um importante problema de saúde pública 24 . 32 . Desta forma, foram observadas densidades maiores dessas bactérias patogênicas, especialmente em sedimentos e mexilhões, e uma parte representativa dessas cepas foi resistente a muitos antibióticos.…”
Section: Discussionunclassified
“…Over the years, resistance to Cephalosporins among members of Enterobacteriaceae has increased mainly due to the spreading of Extended-spectrum B-Lactamases (ESBL) and others antibiotics 29 . The presente study corroborate with this results since it was isolated a siginificant number of E. coli strains resistance to Vancomicin, Erytromicin and Fosfomicin.…”
Section: Comparison Of Bacterial Densities and Resistance…mentioning
confidence: 99%
See 1 more Smart Citation